2020
DOI: 10.1177/0003134820949508
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Hospital/University Affiliation on Research Productivity Among US-Based Authors in the Fields of Trauma, Surgical Critical Care, Acute Care, and Emergency General Surgery

Abstract: Background Research productivity is critical to academic surgery and essential for advancing surgical knowledge and evidence-based practice. We aim to determine if surgeon affiliation with top US universities/hospitals (TOPS) is associated with increased research productivity measured by numbers of peer-reviewed publications in PubMed (PMIDs). Methods A bibliometric analysis was performed for PMIDs. Affiliated authors who published in trauma surgery (TS), surgical critical care (SCC), acute care surgery (ACS),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…There is really no similar evidence in the region with which these results can be contrasted. However, compared to the productivity reported by authors from other continents, the disadvantage and fragmentation of the Colombian surgical scientific production is clearly observed [ [22] , [23] , [24] , [25] ]. Many research groups can be multidisciplinary, where they research on different branches of medical science.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…There is really no similar evidence in the region with which these results can be contrasted. However, compared to the productivity reported by authors from other continents, the disadvantage and fragmentation of the Colombian surgical scientific production is clearly observed [ [22] , [23] , [24] , [25] ]. Many research groups can be multidisciplinary, where they research on different branches of medical science.…”
Section: Discussionmentioning
confidence: 87%
“…Among the bibliometric studies that have analyzed the scientific production of research in Colombian surgery is the one conducted by Sánchez-Jaramillo et al [ 22 ], who studied 20 years of publications on research in surgical education, finding only 63 studies, approximately 40% were published in journals not indexed in medium-high quality bases (ISI/SCOPUS), 20% in Q1 journals, and have an average of 10 citations per article [ 22 ]. Unlike what has been investigated in Colombia, other countries, mainly the United States, have shown a much higher productivity and better quality, represented by a higher percentage of participation in Q1-Q2 journals, better metrics and, in general, being the department with the highest contribution to surgery [ 22 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the presented results, it was impossible to conclude whether the author’s specialty influenced articles publication times. The previous investigation demonstrated that authors' affiliation had an impact on research productivity [ 24 ]. Other studies revealed no or weak associations with the publication times and the author’s specialty [ 1 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] At academic medical centers, which have a research mandate, it is resolved by the leadership helping to define their balance point. 10 At nonacademic medical centers, there is less debate: these are places where clinical work takes precedence, and research is likely not supported as it is arguably not the mission of the institution. Successful research programs, usually associated with the Carnegie classification of Very High-Research Activity Universities, have major laboratory infrastructures, research support, and a commensurate expectation that these appointments lead to scholarship, successes in innovation, publication, and grant funding.…”
Section: Introductionmentioning
confidence: 99%